Aplicación de protocolos y manuales vigentes para la protección y explotación de la escena del crimen en muertes violentas suscitadas en la provincia de Loja durante los años 2015 a 2020 - Moncada Ramírez, Lady Anabel (2023)
The present research entitled: “Application of protocols and manuals in force for the protection and exploitation of the crime scene in violent deaths suscitated in the province of Loja during the years 2015 to 2020”, was raised with the purpose of analyzing the insufficient application of protocols and manuals for the protection and exploitation of the crime scene in violent deaths and its consequences in the criminal system. Criminalistics is a forensic science closely related to the field of crime involving violent deaths, so it is essential to understand some basic concepts of the discipline. To achieve the proposed objectives, the research was based on empirical and descriptive methods, through which prosecutorial files were analyzed, on which there were enforceable sentences in all cases; in addition, through surveys the knowledge of members of the National Police in the prosecution of cases of violent deaths was evaluated and interviews were conducted with judges, public prosecutors in order to obtain information on the impact of inadequate procedure on a scene, in the justice system. The protection and exploitation of the scene by members of the National Police and its influence on the validity of the evidence and its evidentiary effectiveness according to article 76.4 of the Constitution of the Republic was specifically analyzed. A poorly performed or poorly obtained evidence will lack evidentiary effectiveness, and the adulteration, entry or loss of evidence will lead to an erroneous sentence by the Judicial System. Determining that there is a problem regarding the approach to scenes and evidence, which generates a great impact on the prosecution of crimes. Once the problem was identified, the cause of the same was investigated, obtaining as results that the members of the National Police of Preventive Service should be trained in depth in crime scene protection, in Technical Ocular Inspection and handling of evidence in addition to preparation in terms of law. Bad procedures at the scene of a crime result in the conviction of innocent people or the freedom of those responsible for committing punishable acts. Key words: Place of the facts, Violent death, Crime scene, Chain of custody.